2021
DOI: 10.1101/2021.03.25.436974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental characterization ofin silicored-shift predicted iLOVL470T/Q489Kand iLOVV392K/F410V/A426Smutants

Abstract: iLOV is a flavin mononucleotide (FMN)-binding fluorescent protein (FbFP) with excitation and emission spectra similar to those of the green fluorescent protein (GFP). Importantly, contrary to GFP, iLOV fluoresces independently of molecular oxygen, making its usage in low-oxygen conditions possible. Moreover, iLOV is smaller than GFP, increasing the likelihood of retaining full functionality when creating fusions with proteins of interest. Nonetheless, GFP remains to date the most widely used FP in molecular bi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…44 Wehler and co-workers experimentally attempted to prepare these mutants but could not prepare a functional red-shifted FbFP, as they found that a double-point mutant (iLOV-L470T/Q489K) gives a ∼2 nm blue shift and a triple-point mutation (iLOV-V392K/F410V/ A426S) lost the ability to bind the chromophore due to the V392K mutation. 45 Overall, while the strategy of placing a positive charge in the vicinity of flavin's N5 and C4a atoms was theoretically shown to work, most of the amino acids on that side of the protein turned out to be conformationally unstable or essential for chromophore binding. Recently, Rollen and coworkers prepared a red-shifted iLOV with a double-point mutation (iLOV-V392T/Q489K).…”
Section: ■ Introductionmentioning
confidence: 99%
“…44 Wehler and co-workers experimentally attempted to prepare these mutants but could not prepare a functional red-shifted FbFP, as they found that a double-point mutant (iLOV-L470T/Q489K) gives a ∼2 nm blue shift and a triple-point mutation (iLOV-V392K/F410V/ A426S) lost the ability to bind the chromophore due to the V392K mutation. 45 Overall, while the strategy of placing a positive charge in the vicinity of flavin's N5 and C4a atoms was theoretically shown to work, most of the amino acids on that side of the protein turned out to be conformationally unstable or essential for chromophore binding. Recently, Rollen and coworkers prepared a red-shifted iLOV with a double-point mutation (iLOV-V392T/Q489K).…”
Section: ■ Introductionmentioning
confidence: 99%
“…(44) Recently, Wehler and coworkers experimentally attempted to prepare these mutants but could not prepare a functional red-shifted FbFP, as they found that a double-point mutant (iLOV-L470T/Q489K) gives ~2 nm blueshift and a triple-point mutation (iLOV-V392K/F410V/A426S) lost the ability to bind the chromophore due to the V392K mutation. (45) Overall, while the strategy of placing a positive charge in the vicinity of flavin's N5 and C4a atoms was theoretically shown to work, most of the amino acids on that side of the protein turned out to be conformationally unstable or essential for chromophore binding.…”
Section: Introductionmentioning
confidence: 99%